Analisis Kecerdasan Emosional Anak Pengendalian Diri dan Kemampuan Memecahkan Masalah Perspektif al-Qurân Hadits - Amru Almu'tasim (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2019)
This article examines children's emotional intelligence in terms of self-control abilities and problem solving. Emotional intelligence is formed in children so that children are able to control themselves, resist anger, be able to solve problems. Get to know yourself and others. From the results of the study, the authors can conclude that children's emotional intelligence is the dream of every parent because children are able to recognize the emotions of themselves and others, are able to solve problems without causing problems, are able to motivate themselves and have an empathetic attitude. So that children who have emotional intelligence are not easily offended, are not easily ignited by emotions, become children who are polite and patient. The results of this study show that 1). Parents always become exemplary emotion teachers for children, 2). Advise with constructive advice, 3). Give understanding to children with language and tone that is not scary.